2016
DOI: 10.2174/1389450116666150825112623
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Canonical Wnt/β-catenin Signaling in Cartilage Chondrocytes

Abstract: Articular cartilage is a physiologically non-self-renewing avascular tissue with a unique cell type, the chondrocyte, which functions as producing and maintaining the extracellular matrix of cartilage. Cartilage differentiation and maintenance of homeostasis are finely tuned by a complex network of signaling molecules. The network sheds light on these mechanisms that appear to be highly relevant to both the identification of pathogenic key factors, and the development of biological approaches for cartilage reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…cd44 is a downstream target gene of the Wnt/β-catenin signaling pathway, which has been previously reported to be an important signaling pathway, implicated in the chondro-induction differentiation (42,43). MaPK family transduction involves a multistep kinase cascade; erK is a major kinase among MaPKs and has been shown to serve a critical role in mediating chondrogenesis and associated gene expression (29).…”
Section: Discussionmentioning
confidence: 99%
“…cd44 is a downstream target gene of the Wnt/β-catenin signaling pathway, which has been previously reported to be an important signaling pathway, implicated in the chondro-induction differentiation (42,43). MaPK family transduction involves a multistep kinase cascade; erK is a major kinase among MaPKs and has been shown to serve a critical role in mediating chondrogenesis and associated gene expression (29).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous work Xenopus that demonstrated that overexpression of Wnt inhibitors frzb-1 , crescent and dkk similarly resulted in a larger mouths but narrower faces [ 65 ]. Together, work in various vertebrate models indicate that Wnt/beta-catenin inhibitors define the region that will form the embryonic mouth while Wnt/beta-catenin signals are required in the surrounding facial prominences to maintain proliferative regions and direct jaw cartilage development [ 66 70 ]. Thus, disruption of the balance of WNT activation and inhibition can alter the relative facial dimensions in the developing embryo [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…adScs have been demonstrated to differentiate into multiple different cell types, including adipocytes, osteoblasts, chondrocytes and myocytes, in specific inductive conditions (15). due to the multipotent nature of adScs, researchers and clinicians have been exploring their therapeutic potential in various joint disorders, including oa (16). another advantage of adScs is the avoidance of rejection.…”
Section: Discussionmentioning
confidence: 99%
“…in the bones, exosomes regulate multiple signaling processes involved in the differentiation of osteocytes and bone architecture maintenance in a paracrine manner (6). For instance, exosomes were detected in the bone microenvironment, where they modulated intracellular or intercellular signaling, by targeting the same cells, adjacent cells or distant organs (16). exosomes have been considered to be an important component in the delivery of chondrogenic signaling factors for bone regeneration (19).…”
Section: Discussionmentioning
confidence: 99%